Cosmological forecasts from photometric measurements of the angular correlation function for the Legacy Survey of Space and Time. Issue Volume 15:Issue S359(2020) (March 2019) - de Souza, Diogo H. F.; Santiago, Basílio X.
Abstract: We aim to do forecasts for the Legacy Survey of Space and Time (LSST) with a theoretical modeling of the two point angular correlation function. The Fisher matrix is the starting point. This is a square matrix over the cosmological parameters, whose diagonal contains direct informations on the parameters expected uncertainties.